2019
DOI: 10.1111/1467-8462.12348
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy and Financial Stability: The Role of Inflation Targeting

Abstract: This article examines the relationship between Inflation targeting (IT) and financial instability from 1990 to 2015 for Asian economies. To measure financial instability, a multidimensional financial conditioning index is calculated following the ECB's approach. Using a fixed effects panel data model the study finds that adoption of IT policy in Asian economies has an adverse impact on financial stability, thus rejecting the ‘conventional wisdom’ hypothesis. Further, the Vector Autoregression (VAR) result show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
2
8
0
1
Order By: Relevance
“…To achieve this purpose, the time-varying nature of the relationship between the price stability, financial stability, policy interest rate and money supply in the US, where monetary policies are designed to achieve price stability, full employment and moderate long-term interest rate targets, is studied econometrically with the TVP-SVAR model for the period 1993:12-2020:12. The results of the estimated TVP-SVAR models are parallel with the empirical findings of studies by Dhal et al (2011), Blot et al (2015), Sethi & Acharya (2020) and Sahoo (2020), who found mutual relationships between price and financial stability and who corroborate the proposition of the new environment hypothesis in the theoretical literature that price stability may not necessarily guarantee financial stability.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…To achieve this purpose, the time-varying nature of the relationship between the price stability, financial stability, policy interest rate and money supply in the US, where monetary policies are designed to achieve price stability, full employment and moderate long-term interest rate targets, is studied econometrically with the TVP-SVAR model for the period 1993:12-2020:12. The results of the estimated TVP-SVAR models are parallel with the empirical findings of studies by Dhal et al (2011), Blot et al (2015), Sethi & Acharya (2020) and Sahoo (2020), who found mutual relationships between price and financial stability and who corroborate the proposition of the new environment hypothesis in the theoretical literature that price stability may not necessarily guarantee financial stability.…”
Section: Discussionsupporting
confidence: 83%
“…They found that financial stability supports price stability; however, price stability impedes financial stability. Empirical results that support the validity of the new environment hypothesis on the relationship between price and financial stability were found in studies by Blot et al (2015) and Sethi & Acharya (2020). Blot et al (2015) examined the relationship between price stability represented by the actual inflation rate and financial stability calculated in the form of an index that encompasses various indicators related to the stability of the banking and finance sector of the US and countries in the Eurozone for the period 1993: M12-2012: M12 and 1999: M1-2012: M12.…”
Section: Empirical Literaturementioning
confidence: 55%
See 3 more Smart Citations